Site-Specific Nutrient Management for Rainfed Maize in Western Mid-Hills of Nepal - Ghimire, Prakash; Dahal, Khem Raj; Marahatta, Santosh; Devkota, Krishna; Ghimire, Buddhi Raj (International Journal of Applied Sciences and Biotechnology, 2015)
On-farm experiment was conducted in eight farmers’ field, of Khasyoli village development committee (952 to 1415 masl), Nepal, from April to September, 2011 to address the major constraint (nutrient management) to maize production through site-specific nutrient management (SSNM) as this approach is popular among scientists. The experiment comprised three nutrient omission plots (0N, 0P, and 0K), an ample NPK plot, and a farmers’ fertilization practice (FFP) plot, arranged in randomized complete block design. Farmers planted open pollinated variety (Manakamana-3) and managed in their way. Field-specific NPK application rates were calculated by considering nutrient demand, indigenous NPK supply and recovery efficiency of fertilizers. Grain yield in FFP (2.32 Mg/ha) and 0N (1.79 Mg/ha) plots differed significantly from each other and rest of the treatments, but was statistically similar among 0P (3.18 Mg/ha), 0K (3.40 Mg/ha) and ample NPK (3.38 Mg/ha) plots. Post-harvest grain and stover analysis revealed that indigenous NPK supply (20-71 kg N, 19-68 kg P2O5 and 51-164 kg K2O/ha) of soil vary among the farmers’ field. Moreover, soil was poor in indigenous N supply (42 kg/ha), but rich in indigenous P2O5 (35 kg/ha) and K2O (90 kg/ha) supply, on an average. As per the principles of SSNM, the initial fertilizer recommendation made can vary from 40-222 kg N, 0- 93 kg P2O5, and 0-50 kg K2O/ha. On an average, farmers may apply no or lower dose of P2O5 (18 kg/ha) and K2O (3 kg/ha) but need to significantly increase dose of N (143 kg/ha) fertilizer for enhancing soil and maize productivity. Int J Appl Sci Biotechnol, Vol 3(2): 227-231 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12538